Thematic Progression in EFL Students’ Academic Writings: A Systemic Functional Grammar Study - Heri Kuswoyo; Susardi Susardi (Universitas Teknokrat Indonesia, 2016)
This research aims to find out (simple and multiple with two) thematic progression pattern in fifth semester students’ academic writing. It elaborates how the students organize the ideas in their writing through the organization of the theme and rheme. To find out the pattern, the theory of thematic progression patterns proposed by Bloor and Bloor (2004) was applied. Then, descriptive qualitative and library research methods are applied in this research. The data in this research are 20 pieces of fifth semester students’ academic writings. The result of the research shows that there are four types of simple thematic progression pattern and seven types of multiple with two thematic progression pattern found in students’ academic writings. Then, it can be concluded that thematic progression pattern in students’ academic writings, to some extent, are various.